Bomber Harris Sir Arthur Harris' despatch on war operations 1942-1945 - Harris, Arthur Travers (Pen & Sword Aviation, 2014)
The bombing campaign conducted against Germany ... in the Second World War was, and remains, one of the most controversial operations of the entire war. The full text of Harris' despatches is reproduced here along with an explanation why these documents were withheld for so many yuears.